A Single Case Study of Ayurvedic Management of Yakraddalyudara w.s.r. to Hepatomegaly - Meena, Seema; Sharma, Ravi (International Research Journal of Ayurveda & Yoga, 2022)
yurveda has many propositions to hepatobiliary diseases which are akin to modern understanding of hepatology. Besides elaborate clinical descriptions of various hepatic conditions, Ayurveda further proposes many herbal, Herbo mineral and dietary interventions to prevent and to manage such conditions. Kalmegha( Andrographis panniculata ), Bhumiamalki churna, Kutki churna, are trusted drugs from Ayurvedic repertory which is variously used in many hepatic conditions. We had gone through a pilot study to evaluate its role in various hepatic conditions and found that it has a beneficial role in hepatocellular pathologies. The ayurvedic method aims to reduce disability while also easing symptoms. Here, we discuss a case of Yakrddalyudara that was effectively treated by Ayurvedic medicine.